Construction of R-4 terms in N=2 D=8 superspace - Berkovits, N. (Elsevier B.V., 1998)
Using linearized superfields, R-4 terms in the Type II superstring effective action compactified on T-2 are constructed as integrals in N = 2 D = 8 superspace. The structure of these super space integrals allows a simple proof of the R-4 non-renormalization theorems which were first conjectured by Green and Gutperle. (C) 1998 Elsevier B.V. B.V.